The circular nutrient economy of terrestrial ecosystems and the consequences for rock weathering - Maher, Kate; von Blanckenburg, Friedhelm (Frontiers in Environmental Science, 2023)
Earth’s biosphere is thought to exert a substantial influence on regolith evolution and chemical weathering rates. However, ecosystems are also highly efficient at retaining and recycling nutrients. Thus, when the ecological demand for rock-derived nutrients (e.g., P, Ca, K) exceeds the rates of regolith supply, ecosystems use a variety of retention and recycling strategies to armor themselves against nutrient limitations. To evaluate the balance between nutrient recycling and new nutrient input, we combined a plant model that drives growth according to foliar P levels with a weathering model that includes regolith rejuvenation via erosion and export via chemical weathering according to water flow, regolith thickness, mineral dissolution rates, secondary minerals, and nutrient storage in organic and mineral phases. We find that plant growth is strongly dependent on the total regolith nutrient inventory, resulting in a strong correlation between plant productivity and erosion. Increased water export or decreased regolith thickness diminish the total inventory of nutrient corresponding to lower rates of recycling and lower plant growth. In contrast, purported biogenic drivers of weathering, such as enhanced mineral dissolution, only support higher growth rates at high erosion rates. At erosion rates typical of the global land surface, more rapid mineral dissolution combined with enhanced formation of secondary minerals, depletes the inventory of mineral P, resulting in no benefit for plant growth. We also find that the increased chemical weathering export does not scale directly with plant growth. For example, accelerated mineral weathering does increase chemical weathering export but not potential plant growth. Conversely, thicker regolith is associated with a small increase in weathering export, but a large increase in potential plant growth. Collectively, when plant growth is coupled to regolith weathering our calculations suggest that plant productivity is not directly correlated with silicate weathering fluxes, and that biotic drivers of silicate weathering may only be effective at high erosion rates not typical at the Earth’s surface.